Presence in Peru of Mecistocirrus Digitatus (Linstow, 1906) Railliet and Henry, 1912 (Nematoda, Trichostrongylidae, Haemonchinae) - Tantaleán, Manuel (2007)
In this paper, Mecistocirrus digitatus (Linstow, 1906) Railliet and Henry, 1012 a nematode Trichostrongylidae is reported in the fi rst time from Loreto, Peru.